Pre-collegiate factors influencing the self-efficacy of first-year college engineering students - Fantz, Todd Donovan, author; De Miranda, Michael A., advisor; Siller, Thomas J., advisor (Colorado State University. Libraries, 2009)
High attrition rates in engineering schools and a decrease in the number of students pursuing engineering degrees has led to concerns of a shortage of engineering trained professionals. A shortage would threaten national security, economic competitiveness, and social conditions in the United States. Outreach programs consisting of pre-engineering classes, multi-day engineering programs (camps), school-sponsored engineering extra-curricular programs, and single-day engineering workshops have been funded and designed to recruit and prepare K-12 students to study engineering in college. The purpose of this study was to determine the effectiveness of pre-collegiate engineering outreach programs to recruit and prepare future engineering students. Data was collected from 332 first-year engineering students at one university. Students were asked to list and rate their personal engineering experiences and influences to study engineering and their self-efficacy in their engineering courses. Correlation analysis was used to explore linear relationships among demographic factors, pre-collegiate exposure to engineering content, and engineering self-efficacy. Effectiveness of formal and informal pre-collegiate outreach programs and differences between demographic characteristics were examined through regression, ANOVA, and t-test analysis. Results from this research indicate experiences from technology and pre-collegiate engineering programs are a significant source of motivation for students to study engineering. Exposure to engineering content during the pre-collegiate years was also shown to have a positive effect on the students' engineering self-efficacy. In particular, students with formal K-12 technology and pre-engineering coursework had higher self-efficacy scores than those who did not. In addition, students who had hobbies involving computers and programming showed higher self-efficacy scores than the students who did not. Males were found to have statistically significant higher engineering self-efficacy and significantly greater number of pre-collegiate engineering experiences than females. This research adds to the breadth of knowledge about pre-collegiate engineering and technology outreach programs. The data and research findings in this study can inform engineering educators in assessing the effectiveness of pre-collegiate engineering outreach programs to recruit students into engineering programs and prepare them for success.
Keywords: engineering education; engineering outreach; engineering students; first-year students; K-12 pre-engineering; precollegiate; self-efficacy; technology education; women in engineering; engineering; higher education; colleges and universities; engineering schools; students